Recognizing Dignity: Young Black Men Growing Up in an Era of Surveillance - Oeur, Freeden (Tufts University. Tisch Library., 2016)
An enduring finding is that marginalized young men of color aggressively seek “respect,” or masculine status. Drawing on ethnographic fieldwork at an all-boys public high school, the author found that respect—a desire to “be known”—offers an incomplete explanation for how young black men claim recognition in an era of surveillance. These findings reveal an alternative and more complex portrait of criminalized young black men in search of multiple dignities. With the help of adults, the young men in this study made claims to the right to grow as individuals. They also continued to yearn for a form of respect that rejected a sexually victimized identity, in a manner rarely captured in previous research. Their yearnings also highlight claims to a third form of dignity: to “be unknown,” or the privilege of anonymity.